The Influence of Price and Social Media Marketing on The Decision to Use Grabfood in Pontianak City - Muhammad Gilang Pradana; Helman Fachri (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of Price and Social Media Marketing on the Decision to Use GrabFood in Pontianak City. This study employed an associative quantitative approach. The sample consisted of 100 respondents who were residents of Pontianak City, owned the Grab application, and had used GrabFood services. The main data were collected through questionnaires using a 5-point Likert scale, while observation, interviews, and secondary data were used as supporting data. The data were analyzed using multiple linear regression, supported by validity tests, reliability tests, classical assumption tests, correlation coefficient analysis, coefficient of determination, and hypothesis testing through t-tests and F-tests. The results show that all research instruments were valid and reliable. Partially, Price has a positive and significant effect on the Decision to Use, with a t-value of 4.069 and a significance value of 0.000. Social Media Marketing also has a positive and significant effect on the Decision to Use, with a t-value of 3.946 and a significance value of 0.000. Simultaneously, Price and Social Media Marketing have a significant effect on the Decision to Use, with an F-value of 28.950 and a significance value of 0.000. The coefficient of determination (R²) of 0.374 indicates that 37.4% of the Decision to Use GrabFood can be explained by Price and Social Media Marketing, while the remaining 62.6% is influenced by other factors outside this study.